A Study on Construction Risks Prioritization and its Management - B, Subramanyam; Karunya.Nemi Chandran, Nycilin (International Journal of Engineering and Technology, 2018)
Construction industry is an important industry and remains so with the continuation of the development process especially in the developing countries. On the other it is very risk and hazard. As industry when compared to other industries financial losses and bodily injury and death, and resulting human, social impacts are more in the case of construction.Â Mishaps also contain significant costs that are not insurable. Financial deliberations contains direct costs like medical reimbursement andÂ hidden costs includes loss of competence by breaking up crew, cost to train fresh or changed employee, damage to equipment and tools, cost experienced by delays. Many researchers have been suggested risk management techniques to minimize the losses in the industry and very few companies may be implemented the suggestions.Â The goal of this study is to recognize and rank risks in construction projects. This study proposes the hierarchical dependencies between the criteria. The variations and factors have been investigated via questionnaire and is an element of an on-going research into the application of risk management in major projects. To know the performance and applicable of proposed model set of data collected from different industries by using the informal approaches such as intuition and experiences the study is conducted to prioritize and manage risks. Â